(untitled) (Journal of Asian Development Studies, 2020)
The objective of this study is to shift the reserve deposits into the treasuries in order to improve the economic and social justice and less inequality. However, this is a noncontroversial deed and it looks like a sensible approach. The reasons why Islamic finance scores better than the conventional finance to enhance financial inclusion and bring in greater economic and social equity is because it is interest-free and the two pillars of Islam are risk sharing and redistribution of wealth. In order to better understand the 100% reserve banking, first we understand the implications and consequences of banking system and evaluation of money creation, and how institutions control the money and credit supply in the operation market? However, this study suggests some reforms for existing financial system converts into Islamic monetary system through complete reserve banking system.